Tinker Bell's tea party - Bergen, Lara.; Picksey, A.; Disney Storybook Artists (New York : Disney Press, 2008)
Tinker Bell's desire to have a cup of tea in her newly fashioned silver tea cup turns into a lavish tea party with all of her friends.
3.6
K-3
K-3
Keywords: Never-Never Land (Imaginary place) -- Juvenile fiction; Fairies -- Juvenile fiction; Parties -- Juvenile fiction; Friendship -- Juvenile fiction; Never-Never Land (Imaginary place) -- Fiction; Fairies -- Fiction; Parties -- Fiction; Friendship -- Fiction; Never-Never Land (Imaginary place) -- Fiction; Fairies -- Fiction; Parties -- Fiction; Friendship -- Fiction